N-substituted pyrido-1,4-Oxazin-3-ones induce apoptosis of hepatocellular carcinoma cells by targeting NF-kB signaling pathway - Mohan, C.; Bharathkumar, H.; Dukanya; Rangappa, S.; Shanmugam, M.; Chinnathambi, A.; Alharbi, S.; Alahmadi, T.; Bhattacharjee, A.; Lobie, P.; Deivasigamani, A.; Hui, K.; et al. (2018)
Copyright © 2018 Mohan, Bharathkumar, Dukanya, Rangappa, Shanmugam. Hepatocellular carcinoma (HCC) is a fatal disease and ranked fifth in cancer related mortality. Persistent activation of NF-?B is responsible for the oncogenesis, metastasis, tumor evasion, anti-apoptosis, angiogenesis and proliferation in HCC. Therefore, designing of chemically novel, biologically potent small molecules that target NF-?B signaling cascade have gained prominent clinical interest. Herein we synthesized a novel class of 4-(substituted)-2H-pyrido[3,2-b][1,4]oxazin-3(4H)-one by reacting 2H-pyrido[3,2-b][1,4]oxazin-3(4H)-one with various alkyl halides by using combustion derived bismuth oxide. We evaluated the antiproliferative efficacy of newly synthesized compounds against HCC cells and identified 4-(4-nitrobenzyl)-2H-pyrido[3,2-b][1,4]oxazin-3(4H)-one (NPO) as lead anticancer agent. In addition, we investigated the effect of NPO on the DNA binding ability of NF-?B and NF-?B regulated luciferase expression in HCC cells. The results demonstrated that NPO can induce significant growth inhibitory effects in HepG2, HCCLM3 and Huh-7 cells in dose and time-dependent manner. Interestingly, NPO induced significant downregulation in p65 DNA binding ability, p65 phosphorylation and subsequent expression of NF-?B dependent luciferase gene expression in diverse HCC cell lines. Further, in silico docking analysis suggested that NPO can show direct physical interaction with NF-?B. Finally, NPO was found to significantly abrogate tumor growth at a dose of 50 mg/kg in an orthotopic mouse model. Thus, we report the potential anticancer effects of NPO as a novel inhibitor of NF-?B signaling pathway in HCC.